Preparing Educational Leaders: A Roadmap to Success - Michelle D. Young; Meredith Mountford; Gary M. Crow (Educational Considerations, 2005)
Many have argued that educational leadership preparation programs are under siege. Although the mounting national attention can be traced back to the 1980s and perhaps earlier, the past few years have been witness to highly objectionable media commentaries and politicized disputes about leadership preparation.